Design of cascade thermoelectric generation systems with improved thermal reliability. (15th March 2022) - Aljaghtham, Mutabe; Celik, Emrah
Abstract: This paper presents a comprehensive analysis of novel, unileg cascade thermoelectric systems. Unileg systems offer the flexibility of selecting a single (p- or n-) thermoelectric material in a thermoelectric system compared to two (n- and p-) materials. Finite element analysis simulations were performed to design and analyze two and three stages of cascade systems. Simulation results show that unileg cascade systems perform significantly (∼75%) better than their unicouple counterparts in both two and three stage configurations due to the elimination of the poorly performing thermoelectric leg. In addition to the enhanced thermoelectric power generation, thermal stress is lowered in unileg systems since the mismatch of the thermal expansion coefficient originating between different TE legs material can be minimized. Overall, the presented unileg systems show their promise for the future thermoelectric energy generation or cooling applications for electronics. Highlights: Comparison between unicouple and unileg cascade TEG systems is introduced. Thermal reliability and TE performance are investigated for cascade TEG systems. Unileg cascade TEG generates higher TE power and displays lower Von Mises stresses. Unicouple cascade TEG shows higher heat losses compared to unileg cascade TEG. Thomson effect is higher in Unileg TEG compared to unicouple TEG.